MUSIC STRUCTURE ANALYSIS OF THE SONG SUNO LOWALANGI ARRANGEMENT BY BRIAN HAREFA - Galingging, Kamaluddin; Waruwu, Happy Majesty; Saragih, Ronald H; Simangunsong, Emmi; Situmorang, Yulia Ruth (Universitas Negeri Medan, 2025)
This research aims to discuss the structure of the musical arrangement of the song